Website-Based Experiential Learning Cycle Training Management Model To Enhance Professional Competence Of Biology Teachers In Mgmp South Jakarta - Alamsyah, Mashudi; Setyaningsih, Sri; Hardhienata , Soewarto (International Journal Labs, 2025)
Improving teachers' professional competence is the main demand in dealing with curriculum changes and educational technology developments. Biology teachers as part of the implementation of science education are required not only to master the teaching materials, but also to be able to manage innovative and student-centered learning. However, the reality is that there are still many teachers who experience obstacles in implementing experiential learning, both due to limited training and supportive learning media. In addition, conventional training that has been attended by teachers is considered less flexible and ineffective to support in-depth mastery of the material. Therefore, an experiential learning cycle-based training model developed through digital platforms is needed, so that it is able to answer the challenge of developing teachers' professional competencies in a sustainable and flexible manner. The research approach used in this study is the Research and Development (R&D) research method. The data collection techniques used in this study are interview techniques and declassification analysis. The analysis method used in this research and development is an analysis that is able to support the achievement of the goals of research and development activities, namely a website-based experiential learning cycle training management model. Based on the results of theoretical studies, regulations, and needs analysis in the field, a website-based experiential learning cycle training model has been developed which is packaged in an application called LearnPress, in order to improve the professional competence of teachers in Indonesia. This model is designed in accordance with the concept of experiential learning and teacher competency strengthening policies. The validation results from the material experts showed that the training content was very good in supporting the mastery of biology material, while the validation from the media expert confirmed the feasibility of the display, navigation, and interactivity of the website as a digital learning medium. Effectiveness tests through various stages of scale show that LearnPress is highly effective and contributes positively to improving teachers' professional competence.